Hepatic S6K1 Partially Regulates Lifespan of Mice with Mitochondrial Complex I Deficiency - Ito, Takashi K.; Lu, Chenhao; Khan, Jacob; Nguyen, Quy; Huang, Heather Z.; Kim, Dayae; Phillips, James; Tan, Jo; Lee, Yenna; Nguyen, Tuyet; Khessib, Samy; Lim, Natalie; et al. (Frontiers in Genetics, 2017)
The inactivation of ribosomal protein S6 kinase 1 (S6K1) recapitulates aspects of caloric restriction and mTORC1 inhibition to achieve prolonged longevity in invertebrate and mouse models. In addition to delaying normative aging, inhibition of mTORC1 extends the shortened lifespan of yeast, fly, and mouse models with severe mitochondrial disease. Here we tested whether disruption of S6K1 can recapitulate the beneficial effects of mTORC1 inhibition in the Ndufs4 knockout (NKO) mouse model of Leigh Syndrome caused by Complex I deficiency. These NKO mice develop profound neurodegeneration resulting in brain lesions and death around 50-60 days of age. Our results show that liver-specific, as well as whole body, S6K1 deletion modestly prolongs survival and delays onset of neurological symptoms in NKO mice. In contrast, we observed no survival benefit in NKO mice specifically disrupted for S6K1 in neurons or adipocytes. Body weight was reduced in WT mice upon disruption of S6K1 in adipocytes or whole body, but not altered when S6K1 was disrupted only in neurons or liver. Taken together, these data indicate that decreased S6K1 activity in liver is sufficient to delay the neurological and survival defects caused by deficiency of Complex I and suggest that mTOR signaling can modulate mitochondrial disease and metabolism via cell non-autonomous mechanisms.